VP63 EUnetHTA Planned And Ongoing Projects Database: Usage And Challenges. (2019) - Erdos, Judit; Chalon, Patrice
Abstract : Introduction: The European Network for Health Technology Assessment (EUnetHTA) Planned and Ongoing Projects (POP) database allows sharing information on projects of HTA organisations participating in EUnetHTA. It enables users identifying overlaps and therefore has the potential to reduce duplication of work on similar topics. The aim of our research was to examine the usage of the database, how it helps to reduce duplication, and identify challenges to be addressed. Methods: We conducted a systematic data collection and analysis on the topic overlaps retrospectively and complemented it with an electronic survey aimed at database users. The dataset on the overlaps was collected between June 2016 and September 2017. The survey was conducted in October 2017. Results: During the data collection period, the POP database contained on average 800 projects provided by around fifty percent of the EUnetHTA partner organisations. One hundred and sixty nine identical projects could be identified from which ninety-two percent had different starting dates. Twenty-five percent of the identical projects were elaborated on by three organisations, 10 percent by four, and 6.5 percent by five organisations. Analysis of the survey showed a pattern of "wait and see": users are informed about what other EUnetHTA partners are working on, wait for a finalised HTA or exchange the project plan, search strategies, search results, extraction tables, etc. The data collection and survey could not provide a precise number of collaborations initiated based on information gathered from the database. Conclusions: The POP database is suitable for information sharing and has the potential to save time and resources at EUnetHTA partners. The collaboration is hindered by differences in national processes, including the timing and scope of the assessments. The impact of the POP database on the facilitation of collaboration and reduction of duplication of HTAs produced by EUnetHTA partners is yet to be strengthened.